'Fansens' are waving through a window: Exploring the Dear Evan Hansen fan phenomenon. (1st June 2020) - Walczer, Jarrod; Baird, Derek E.
Dear Evan Hansen (DEH) is a social media-centric musical that has been widely celebrated by a show-specific online fan community, known as 'Fansens', on Instagram and Tumblr, having won the Tony Award for Best Musical in 2017. The growth of this fandom, on these platforms, is unique as Fansens have adopted plot points and thematic elements from the musical relating to how social media affects social anxiety, depression and suicide to create fan art and fanfictions that, in turn, result in a community of care on social media where fans can discuss their own encounters with social anxiety, teen suicide and cyberbullying. Though most Fansens would not have been able to see the musical performed on Broadway or live in-person, their fanfictions, personal posts and fan art reflect and refract the difficulties that young people have with mental health, social anxiety and suicide. Using both digital methods and post-structuralist textual analysis, this article analyses numerous fan cultural artefacts collected from DEH-specific hash-tagged posts on Tumblr and Instagram. In doing so, this article provides a new perspective on the role that fan communities, their artefacts, their use of digital medi, and their fan activist and upstanding techniques can play in providing avenues of self-care and modelling positive online support for those dealing with mental health issues.